Hubungan Sosial Masyarakat Muslim Dan Non Muslim (Studi Deskriptif Di Kelurahan Bincar Kota Padang Sidempuan ) - Jannus Parulian Sihombing; Ulung Napitu; Joni Wilson Sitopu (Journal on Education, 2023)
Abstract This study aims to examine the pattern of social relations between Muslims and non-Muslims in Bincar Village, Padang Sidempuan City and to examine the factors that influence the social relations of Muslim and non-Muslim communities in Bincar Village, Padang Sidempuan City. The research method used in this study is a qualitative research method with a descriptive approach, namely by conducting interviews with Muslim and non-Muslim communities in the Bincar Village. This research was conducted in December 2022. Based on the results of the research, it shows that: I. Patterns of social relations between Muslim and non-Muslim communities, Kel. Bincar Kota Padang Sidempuan consists of an associative process and a dissociative process. The associative process includes: a) Collaboration, such as community service, helping and condolences carried out by Muslim and non-Muslim communities in Bincar Village, b) Assimilation in this case mixed marriages that have occurred in Bincar Village between Muslims and Non-Muslims -Muslims, c) Accommodation, Muslim and non-Muslim communities can place issues of religion and society according to circumstances. The dissociative process includes: competition, contradiction, and conflict/dispute. However, of the three dissociative parts, there is only competition. Contraventions and conflicts/disputes do not occur. The competition in question is healthy and sporty competition. A form of competition in terms of the economy, where Muslim and non-Muslim communities compete in terms of meeting their needs by trading. II. Factors that influence social interaction: a) imitation factor. The people in the Bincar Sub-District are used to the prevailing customs and customs, therefore the Non-Muslim community who are migrants to the Bincar Sub-District respect and respect each other such as when there is a party they attend, grieve when there are neighbors or bereaved relatives. b) sympathy factor. Muslim and non-Muslim communities care for each other, be it when neighbors or relatives suffer a disaster, they help each other. The implications of this research are based on research, namely: For Muslim communities and non-Muslim communities in Bincar Village, to continue to establish cooperation between fellow religious communities so that a harmonious life can be created which leads to tolerance because it is seen as a buffer for survival in times of will come.